Comparison of Active Aging Indicators and Associated Factors Among Urban and Rural Elderly in Behshahr, Iran (2023) - Nadia Khakzad; Ehteramsadat Ilali; AbolfazlHosein Nattaj; Tahereh Yaghoobi (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Active aging involves optimizing opportunities to enhance the quality of life in older age. Environmental differences and lifestyle variations between urban and rural areas can significantly affect active aging. This study aimed to compare the indicators of active aging among elderly individuals in urban and rural areas of Behshahr, while also identifying the factors associated with these indicators in 2023. Materials and methods: This cross-sectional, descriptive-analytical study employed a proportional quota sampling method to examine 350 elderly individuals from comprehensive health service centers in Behshahr. The tools used included a demographic-social factors form and a 40-item questionnaire on the Iranian Active Aging Index. Collected data were analyzed using SPSS version 20 and linear regression tests. Results: The mean age of the elderly participants was 70.96±13.8 years. Among the participants, 52% were men, and 61% were married. The average scores on the Active Aging Index were 111.47±30.48 for urban residents and 93.73±21.66 for rural residents, demonstrating that urban elderly individuals had significantly higher scores than their rural counterparts (P<0.001). Married elderly individuals in both groups scored significantly higher on the Active Aging Index compared to single individuals. Participants with higher education levels and income also achieved significantly greater scores. In contrast, an increase in age and the number of children was associated with a notable reduction in the Active Aging Index score (P<0.05). Conclusion: Attention to geographical, cultural, and social differences is crucial when formulating policies for the elderly. Furthermore, there is an urgent need to develop infrastructure that improves access to health and social services for older adults in rural areas. These findings can guide policymakers in enhancing the quality of life for older adults, highlighting the importance of addressing the unique needs of diverse groups.